A study to explore the emotional intelligence and stress coping strategies among nursing students in selected colleges at Namakkal District- Hermeneutic phenomenological circle approach - Jothilakshmi , K. (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
Background: Emotional intelligence of nursing students helps them to adopt  a healthy life style during stress.Coping is one of the wise choices of avoiding  frustration which is the end product of stress and burnout. If individual want to  handle the stress with effective and appropriate coping he or she should be an  emotionally competent with high emotional intelligence. Methods: Participants  were selected based on trait exhibited by particular group of interest. So adopted  purposive homogenous sampling method for this study. After receiving informed  oral consent students at Dhanvantri College of Nursing, Namakkal were adopted  as participants for this study .With 5 participant’s data saturation point has  been reached and preceded for the analysis. As this study aimed to explore the  phenomenon of EI on coping strategy and to provide wide knowledge regarding  the phenomenon there was a need to fuse individual’s subjective experience  with the hermeneutic circle. So as this study design was Qualitative hermeneutic  Phenomenological circle. Age and Birth order of the participants were demographic  variable. To understand the concept of EI semi structured questions were framed  on the basis of EI domains, all the verbatim reports were analysed by following  interpretative phenomenological analysis and coping strategy of participants were  expressed by the parent of the participants through mobile phone were recorded  and analysed. Results:Participants with high emotional intelligence always deals  the stress with their route cause and handle it easily in a problem focused style.  Whereas Participants with low emotional intelligence deals stress with emotional  focused strategy. And one more new concept (serendipity) were identified that  birth order of the participants has greater influence on coping that is those born  as second and fourth child shown problem focused coping strategy than the  participant who born as first child.
Keywords: Emotional intelligence; Stress coping strategies; Nursing students; Hermeneutic; Phenomenological circle